Faculty development for supervisors of medical student rural attachments in Zimbabwe - Fiona Makoni; Zandile Mafi; Sunanda Ray (AOSIS, 2024)
Reflective writing and keeping portfolios during rural hospital attachments has been shown to give medical students more confidence, better communication skills and clinical competence, thereby making them stronger adult learners. The role of supervisors as facilitators of learning during Community-based Education rural site visits is critical. The University of Zimbabwe Faculty of Medicine and Health Sciences established faculty development workshops to train supervisors to be better able to support students in becoming active learners and critical thinkers, giving them constructive feedback, and encouraging them to look for positive outcomes during their rural attachments. These educational skills were new to most supervisors, requiring a culture change from the usual didactic approaches. Educators had to learn about adult learning theories, the constructivist approach to knowledge creation, role-modelling and methods of assessment that were empowering for students. They were encouraged to form communities of practice through the faculty development process of training and assessment and to consider how to develop research and scholarship in documenting their experiences as facilitators and learning partners with their students and colleagues. These activities enhanced their professional identity formation as scholars, educators and facilitators. Their exposure to the functioning of rural hospitals, partly through narratives of the students' reflective writing, enabled them to develop a greater appreciation of the potential of primary care and the district health services as the foundation of the Zimbabwe health system. Future benefits could include application of this training to other health professional programmes, as part of interprofessional education.